Characteristics of a structural model for the formation of future medical bachelor nurses the readiness for professional activity on the praxeological basis and the results of its practical implementation - Лісна-Міськів, Н. Є. (Scientific notes of the pedagogical department, 2018)
Modern Ukrainian society has a fundamental need to form global professional thinking and a high level of readiness for professional activity of future medical bachelor nurses during the studying. It was determined that pedagogical modeling allows to achieve a qualitatively new level of professional training of future specialists. The article focuses on the description of the potential of pedagogical modeling for the improvement of the professional training of future medical bachelor nurses. Pedagogical modeling is understood as a creative means of knowledge, which reflects the laws and patterns of development of the object under the study. Based on the use of pedagogical modeling, a model has been developed. The model is considered as an integral system consisting of interconnected blocks, which are aimed at a concrete result - the formation of future medical bachelor nurses all indicators of readiness for future professional activity on praxeological basis. The algorithm for constructing a model is based on the use of parametric, component, structural and functional analysis. Structural is a model that consists of a set of specific structural units that cover the specific elements between which a clear relationship is established. The components include: 1) the goal; 2) task; 3) effective approaches, principles and laws; 4) educational environment; 5) organizational and pedagogical conditions; 6) forms of organization of educational process; 7) methods; 8) means; 9) the components, criteria and readiness levels of future medical bachelor nurses for professional activity; 10) expected result. The model reflects the causal relationships between the process of formation of the readiness of future medical bachelor nurses to professional activities. All segregated components are grouped into specific blocks based on logic and consistency. The following blocks are distinguished: purposeful, content, technological, active and productive. Consequently, the model has a block structure and reflects the content of the formation of the readiness of future medical bachelor nurses for professional activity on the praxeological basis. In the process of practical implementation, attention is focused on the properties of the model, which will have an impact on improving the readiness of future medical bachelor nurses to professional activities.